Insights into the role of DNA methylation in diatoms by genome-wide profiling in Phaeodactylum tricornutum - Veluchamy, Alaguraj (2013)
DNA cytosine methylation is a widely conserved epigenetic mark in eukaryotes that appears to have critical roles in the regulation of genome structure and transcription. Genome-wide methylation maps have so far only been established from the supergroups Archaeplastida and Unikont. Here we report the first whole-genome methylome from a stramenopile, the marine model diatom Phaeodactylum tricornutum. Around 6% of the genome is intermittently methylated in a mosaic pattern. We find extensive methylation in transposable elements. We also detect methylation in over 320 genes. Extensive gene methylation correlates strongly with transcriptional silencing and differential expression under specific conditions. By contrast, we find that genes with partial methylation tend to be constitutively expressed. These patterns contrast with those found previously in other eukaryotes. By going beyond plants, animals and fungi, this stramenopile methylome adds significantly to our understanding of the evolution of DNA methylation in eukaryotes.